“O GRANDE FAXINAL DE SÃO MATEUS DO SUL-PR E SUA RELAÇÃO COM A PETROBRAS” - Deina, Mário Sérgio (2018)
This work brings the often conflictual relations between Petrobrás / SIX, installed in the municipality of São Mateus do Sul, and the inhabitants of territorial areas without municipality, expropriated periodically for the expansion of the shale mine (pirobetumino leaflets); the formation and consolidation of the faxinal way of life in the studied area, the classification as the convention and traditionally occupied lands, discussing a relation with the faxinal man with a land that refers to its property, its use and its occupation, the sport social, cultural and economic, customs and secular traditions typical of the Center-South of the Paraná state. The tensions and negative effects on miseries are dealt with in the light of multilevel power relations, both by the state through its oil presence and by the inhabitants of the study area itself; analyzes the future possibilities for the region, considering that the expansion process will be expansion, since shale is a primary process for the production of the oil and other derivatives production unit.